(untitled) (Research, Society and Development, 2024)
The history of human labor has been marked by transformations influenced by the evolution of the means of production and social demands. In Brazil, the rise in unemployment has led many to become informal workers, especially transportation and delivery apps. This article aims to analyze the impact of uberization on the definition of the employment relationship, focusing on the requirements of the employment relationship and the situation of app drivers, considering the possible paths of labor regulation. The methodology used to carry out this study is documentary, qualitative and reflective research. The study examines Brazilian labor legislation, which defines the employment relationship on the basis of personality, non-occurrence, remuneration and legal subordination. Uberization, characterized by flexibilization and deregulation, presents regulatory and economic challenges. Case law shows divergences in the interpretation of the employment relationship between drivers and digital platforms, with decisions both in favor and against recognizing this relationship. This decision could redefine labor legislation in the face of new forms of work. While uberization offers employment alternatives, it also poses risks of job insecurity. A balanced approach that protects workers’ rights while reaping the benefits of technological innovation is essential.